Noninvasive Brain Stimulation for Nicotine Dependence in Schizophrenia: A Mini Review - Ward, Heather Burrell; Brady, Roscoe O.; Halko, Mark A.; Lizano, Paulo (Frontiers in Psychiatry, 2022)
Individuals with schizophrenia are 10 times more likely to have a tobacco use disorder than the general population. Up to 80% of those with schizophrenia smoke tobacco regularly, a prevalence three-times that of the general population. Despite the striking prevalence of tobacco use in schizophrenia, current treatments are not tailored to the pathophysiology of this population. There is growing support for use of noninvasive brain stimulation (NIBS) to treat substance use disorders (SUDs), particularly for tobacco use in neurotypical smokers. NIBS interventions targeting the dorsolateral prefrontal cortex have been effective for nicotine dependence in control populations—so much so that transcranial magnetic stimulation is now FDA-approved for smoking cessation. However, this has not borne out in the studies using this approach in schizophrenia. We performed a literature search to identify articles using NIBS for the treatment of nicotine dependence in people with schizophrenia, which identified six studies. These studies yielded mixed results. Is it possible that nicotine has a unique effect in schizophrenia that is different than its effect in neurotypical smokers? Individuals with schizophrenia may receive additional benefit from nicotine's pro-cognitive effects than control populations and may use nicotine to improve brain network abnormalities from their illness. Therefore, clinical trials of NIBS interventions should test a schizophrenia-specific target for smoking cessation. We propose a generalized approach whereby schizophrenia-specific brain circuitry related to SUDs is be identified and then targeted with NIBS interventions.